2016
DOI: 10.1177/1550059416640441
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of EEG in Attention Deficit Hyperactivity Disorder: A Replication Study

Abstract: The routine use of stimulants in pediatrics has increased dramatically over the past 3 decades and the long-term consequences have yet to be fully studied. Since 1978 there have been 7 articles identifying electroencephalogram (EEG) abnormalities, particularly epileptiform discharges in children with attention deficit hyperactivity disorder (ADHD). Many have studied the prevalence of these discharges in this population with varying results. An article published in 2011 suggests that EEG technology should be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They found high rates of IEDs have been found in specific diagnostic categories such as panic and anxiety disorders, mood disorders, schizophrenia, eating disorders, personality disorders, and violent behavior. Additionally, high rates of IEDs have been found specific to childhood disorders such as ADHD (Kanazawa, 2014;Lee, Choi, Yoon, & Bahn, 2015;Milichap, Stack, & Millichap, 2011;Swatzyna, Tarnow, Roark, & Mardick, 2017a) and Autism Spectrum Disorder (Chez et al, 2006;Mulligan & Trauner, 2013;Reinhold, Molloy, & Manning-Courtney, 2005;Swatzyna 2017b;Yasuhara, 2010). We present the findings of our systematic review of the literature and compare them to our crosssectional analysis in order to determine prevalence rates of IEDs within diagnostic categories.…”
Section: Ronald Swatzyna and Meredith Hoffmanmentioning
confidence: 96%
“…They found high rates of IEDs have been found in specific diagnostic categories such as panic and anxiety disorders, mood disorders, schizophrenia, eating disorders, personality disorders, and violent behavior. Additionally, high rates of IEDs have been found specific to childhood disorders such as ADHD (Kanazawa, 2014;Lee, Choi, Yoon, & Bahn, 2015;Milichap, Stack, & Millichap, 2011;Swatzyna, Tarnow, Roark, & Mardick, 2017a) and Autism Spectrum Disorder (Chez et al, 2006;Mulligan & Trauner, 2013;Reinhold, Molloy, & Manning-Courtney, 2005;Swatzyna 2017b;Yasuhara, 2010). We present the findings of our systematic review of the literature and compare them to our crosssectional analysis in order to determine prevalence rates of IEDs within diagnostic categories.…”
Section: Ronald Swatzyna and Meredith Hoffmanmentioning
confidence: 96%
“…If administered oblivious to the possibility of concomitant subtle seizures, these medications may precipitate a frank epileptic attack (for which neither the patients nor the clinicians may be prepared) and cause worsening of the depressive state. In managing patients with attention deficit hyperactivity disorder (ADHD), several researchers have observed that the removal of medication that lowers seizure threshold coupled with the addition of an anticonvulsant has resulted in outcomes based on which they have recommended stabilisation of IEDs to ensure effective therapy,40 41 thus underscoring the utility of an EEG. In accordance with evidence from the same studies on ADHD,40 41 the author opines that the failure of antidepressants in a significant number of patients with depression could be due to a possibility of concomitant undetected epilepsy or IEDs that can also contribute to the symptomatology of depression, in which case the utility of an EEG cannot be overemphasised.…”
Section: Author’s Postulationmentioning
confidence: 99%
“…In managing patients with attention deficit hyperactivity disorder (ADHD), several researchers have observed that the removal of medication that lowers seizure threshold coupled with the addition of an anticonvulsant has resulted in outcomes based on which they have recommended stabilisation of IEDs to ensure effective therapy,40 41 thus underscoring the utility of an EEG. In accordance with evidence from the same studies on ADHD,40 41 the author opines that the failure of antidepressants in a significant number of patients with depression could be due to a possibility of concomitant undetected epilepsy or IEDs that can also contribute to the symptomatology of depression, in which case the utility of an EEG cannot be overemphasised. Thus, in patients with depression with IEDs, stabilisation of IEDs by an antiepileptic can function as a priming effect for antidepressants.…”
Section: Author’s Postulationmentioning
confidence: 99%
“…In past research, IEDs have been found to be highly prevalent in certain psychiatric populations. For example, Millichap et al, 13 and Swatzyna et al 14 found a high prevalence of IEDs in ADHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…IEDs represent a dysregulated focus isolated to one part of the brain that is not likely to develop into a seizure focus but would possibly respond well to an AED intervention. It has been suggested that AEDs be considered when IEDs have been identified, 13,14,20 but there is a paucity of research to confirm this.…”
Section: Introductionmentioning
confidence: 99%